RNA-binding protein FXR1 drives cMYC translation by recruiting eIF4F complex to the translation start site - George, Jasmine; Li, Yongsheng; Kadamberi, Ishaque P.; Parashar, Deepak; Tsaih, Shirng-Wern; Gupta, Prachi; Geethadevi, Anjali; Chen, Changliang; Ghosh, Chandrima; Sun, Yunguang; Mittal, Sonam; Ramchandran, Ramani; et al. (Cell reports (Cambridge), 2021)
Fragile X-related protein-1 (FXR1) gene is highly amplified in patients with ovarian cancer, and this amplification is associated with increased expression of both FXR1 mRNA and protein. FXR1 expression directly associates with the survival and proliferation of cancer cells. Surface sensing of translation (SUnSET) assay demonstrates that FXR1 enhances the overall translation in cancer cells. Reverse-phase protein array (RPPA) reveals that cMYC is the key target of FXR1. Mechanistically, FXR1 binds to the AU-rich elements (ARE) present within the 3′ untranslated region (3′UTR) of cMYC and stabilizes its expression. In addition, the RGG domain in FXR1 interacts with eIF4A1 and eIF4E proteins. These two interactions of FXR1 result in the circularization of cMYC mRNA and facilitate the recruitment of eukaryotic translation initiation factors to the translation start site. In brief, we uncover a mechanism by which FXR1 promotes cMYC levels in cancer cells. [Display omitted] •CNVs of FXR1 associate with its expression in ovarian cancer•FXR1 promotes the survival and proliferation of ovarian cancer cells•FXR1 binds to AU-rich elements (ARE) within 3′UTR of cMYC•FXR1 promotes the recruitment of eIF4F complex to translation initiation site George et al. demonstrate that FXR1 binds to the AREs within the 3′UTR of MYC mRNA and improves its stability. The authors also show that the RGG domain of FXR1 interacts with eIF4A1 and eIF4E and facilitates recruitment of the eIF4F complex to translation initiation sites for cMYC translation.